Competitiveness and internationalization of a Portuguese SME in the cheese market - marketing mix and budget - Reis, Patrícia Bitton Parreira Pestana (2021)
S4, an experienced Portuguese cheese company leader in the domestic fresh segment, aims to expand and consolidate its business internationally. By screening several countries based on macro and industry-specific indicators and conducting an in-depth analysis of the four most promising ones, United States and Germany resulted to be the most attractive markets for S4’s internationalization. Following, the most suitable entry mode was defined as well as the ideal business model and marketing plan to effectively run a business in both countries. Financial projections and risk evaluations were performed to assess the viability of the proposed international plan.